Karakter Morfologi dan Fisiologi yang Berkaitan dengan Efisiensi Pemakaian Air pada Beberapa Varietas Padi Gogo - Munawaroh, Laili; Sulistyono, Eko; Lubis, Iskandar (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTUpland rice cultivation required specific cultivation, particularly the use of crop varieties that have good water-use efficiency or varieties that are able to adapt to the conditions of limited water availability. The aim of this study was to describe characters of morphology and physiology related to water use efficiency of upland rice varieties. The research was conducted from October 2013 to April 2014 in the greenhouse IPB Experimental Station Cikabayan, Bogor. The research was arranged in randomized block design with two factors. The first factor was 5 upland rice varieties (Inpago 5, Batutegi, Jatiluhur, Inpago 8 and Sarinah). The second factor was 4 irrigation intervals which were 3, 6, 9, and 12 days. Characteristics assosiated with water saving of upland rices were higher plant height, longer panicle, larger roots volume, narrower leaves, higher evapotranspiration, faster flowering phase, greener leaves, higher number of leaves and tillers, heavier dry matter, higher number of grains, heavier 100 grain weight and dry weight of grains. The fraction of available absorbed water at panicle  initiation,  flowering  and  harvesting  were 83.36%, 137.14% and 116.65%, respectively, to obtain dry grains of 3.39 ton ha-1.Keywords: evapotranspiration, water fraction, WUE